Determination and Mapping of the Causes of High Risk of Earthquake Hazards Using Geoelectrical Data in Bengkaung, Batu Layar, West Lombok Indonesia - Hiden Hiden; Suhayat Minardi; Syamsuddin Yasin; Bakti Sukrisna; Teguh Ardianto (Postgraduate, University of Mataram, 2022)
The Bengkaung area, Batulayar District, West Lombok is suspected to be very vulnerable to the risk of earthquake hazards. However, in this area no scientific research, either geological or geophysical, has ever been carried out regarding this hazard. How are the physical characteristics of the lithology and structure in the area to the risk of earthquake disaster? The purpose of this study was to determine the physical characteristics of the lithology and subsurface structures that were validated by the level of damage. The method used is the geoelectric method and local building damage data. The results of the 2D geoelectric anomaly modeling show the characteristics of the subsurface lithological layers in the form of sand, sandstone, clay, andesite lava faults, fresh andesite lava, and granite. The fault was detected in the center of the study area in a north-south direction. Earthquake hazard analysis shows that the cause of the high risk of earthquake hazard in Bengkaung Village is the presence of faults and cohesive lithology. The highest potential risk is in the southern part of Bengkaung Village. The southern area of ​​Bengkaung Village is dominated by clay that has cohesive properties, especially on the surface. The western and northern parts of Bengkaung Village have medium and low vulnerability to earthquake hazards. The last two areas are dominated by non-cohesive soils in the form of sandy soils and lapilli pumice